Analysis of the Effectiveness and Efficiency of Expenditure Budget Management in the Context of Assessing Financial Performance at the Bogor City Social Service - Kurniawan, Dwi; Sasongko, Hendro; Hardiyanto, Arief Tri (UNIVERSITAS PAKUAN, 2024)
This study aims to find out whether the budget management of the Bogor City Social Service is good, namely in accordance with applicable methods, guidelines, regulations, standards, and systems and to find out the financial performance of the Bogor City Social Service for the 2018-2022 fiscal year reviewed from the efficiency element, and to find out the performance of the Bogor City Social Service for the 2018-2022 fiscal year reviewed from the effectiveness element. The objects of research are data from the Budget Realization Report (LRA) and data from the Performance Report of Government Agencies (LKIP) for the 2018-2022 fiscal year. The data collection methods used are observation methods, interviews, and documentation methods. The data analysis techniques used are quantitative descriptive analysis on efficiency measurement, and effectiveness, qualitative descriptive analysis to find out and analyze budget management. Based on the results of the study, it shows that the budget management of the Bogor City Social Service has been good because it has followed the applicable and established rules, guidelines, standards, and systems. Based on the results of the study, it shows that the management of the budget at the Bogor City Social Service in 2018-2022 from the effectiveness element as an average effectiveness ratio of 103%, it can be said that for 5 years the 2018-2022 period has been effective and the financial performance achievements of the Bogor City Social Service have been able to meet the performance targets that have been set. From the efficiency element, it shows that the budget manager at the Bogor City Social Service on average the efficiency ratio from the 2018-2022 fiscal year is 122%, meaning that during the 5-year period from the 2018-2022 fiscal year, the Bogor City Social Service has been efficient and able to meet the performance targets and budget targets that have been set.